Temporal Trends in the Utilization and Survival Outcomes of Lobar, Segmental, and Wedge Resection for Early-Stage NSCLC, 2004 to 2020 - Eden Z. Deng, BS; Xiaofei Wang, PhD; Jianrong Zhang, MD, MPH; Thomas E. Stinchcombe, MD; Chi-Fu (Jeffrey) Yang, MD; Nasser Altorki, MD (JTO Clinical and Research Reports)
Introduction: Although lobectomy has long been the standard of surgical treatment for early-stage NSCLC, segmental and wedge resections have become another option often used over the past two decades. Methods: To examine the trends over time in the utilization, quality, and overall survival (OS) differences of lobectomy, segmentectomy, and wedge resection, we performed an observational, population-level study of 76,466 patients with T1 or T2 N0M0 NSCLC tumors 2 cm or less in size in the National Cancer Database, from 2004 to 2020. To compare the OS of the three treatments, we used inverse probability of treatment weighting to analyze a subgroup of cases with nodal examination and minimal comorbidity burden. Results: From 2004 to 2020, the use of lobectomy decreased from 75.2% to 67.6% of resections, wedge remained relatively stable (20.5%–22.8%), and segmentectomy increased from 4.3% to 9.7%. The likelihood of nodal assessments and negative margins has increased for all treatments. Younger patients, patients with low comorbidity burden, and patients with smaller tumors have become increasingly likely to receive segmental and wedge resections. Five-year OS of segmentectomy (80.6%, 95% confidence interval [CI]: 78.1%–83.2%) remained noninferior to lobectomy (83.6%, 95% CI: 83.1%–84.1%]), whereas wedge resection was inferior until 2016 to 2019 (five-y OS = 79.9%, 95% CI: 75.9%–83.8%). Conclusions: Sublobar resections, particularly segmentectomies, have increased in frequency and quality. The growing use of sublobar resections for younger and healthier patients highlights the need for additional clinical evidence demonstrating whether these trends do indeed lead to better outcomes.